A minimized symbiotic gene set from the 1.68 Mb pSymB chromid of Sinorhizobium meliloti reveals auxiliary symbiotic loci - Jason V. S. Kearsley; Barney A. Geddes; George C. diCenzo; Maryam Zamani; Turlough M. Finan (BMC Biology)
Abstract Background Symbiotic nitrogen-fixation between bacteria called rhizobia and leguminous plants is a critical aspect of sustainable agriculture. Complex, two-way communication governs the invasion of plant roots and the formation of nodules in which the rhizobia reduce N2 to bioavailable ammonia. Research has uncovered many of the genes required for the symbiosis; however, engineering the symbiosis to function with alternative hosts such as cereal crops necessitates the establishment of a core set of symbiotic players. Results We examined the symbiotic relevance of the genes on the 1.68 Mb pSymB chromid of the model rhizobium Sinorhizobium meliloti. By employing a strain in which pSymB was removed, we used a gain-of-function approach to assess a select group of known symbiotic regions totalling 261 kb (15.5%) of pSymB. This gene set enabled symbiotic N2-fixation with alfalfa with a high degree of plant genotype-dependent variation in which nodules often senesced prematurely. We demonstrate that additional regions lacking canonical symbiosis genes are important for the efficient formation of symbiosis with the plant host. These regions appear to contain auxiliary symbiotic loci whose genes encode products with quasi-essential functions for the symbiosis and that are redundant in nature. We further established a 673-kb pSymB genome that engages consistently in N2-fixation with alfalfa with 45% efficiency. Conclusions The reduction of the pSymB genome showcases the complexity and nuance of its involvement in the N2-fixing symbiosis.